New methods and algorithms of the multifunctional optimization for CAE-system of some technological processes - O. I. Chichko (Литьë и металлургия, 2003)
There are offered the models and algorithms for solution of the technological tasks, connected with optimization of the melts stream processes in gating systems and also for optimization of the process of the industrial details thermal treatment. The algorithms are based on using of design functions of distribution of the object elements on temperatures, speeds, tensile and compressive stresses, received in computer systems “ProLit” and “Pro Therm”.